Child of the flower-song people : Luz Jiménez, daughter of the Nahua - Amescua, Gloria (Abrams Books for Young Readers, 2021)
"As a young Nahua girl in Mexico during the early 1900s, Luz learned how to grind corn in a metate, to twist yarn with her toes, and to weave on a loom. But when the Mexican Revolution came to her village, Luz and her family were forced to flee and start a new life. In Mexico City, Luz became a model for painters, sculptors, and photographers--artists interested in showing the true face of Mexico and not a European version. Through her work Luz found a way to preserve her people's culture by sharing her native language, stories, and traditions. This moving, beautifully illustrated biography tells the remarkable story of how model and teacher Luz Jiménez became "the soul of Mexico"--a living link between the indigenous Nahua and the rest of the world. Through her deep pride in her roots and her unshakeable spirit, the world came to recognize the beauty and strength of her people." -- adapted from jacket flap.